Outcome of pregnancy in women with congenital shunt lesions. Issue 3 (1st March 1999) - Zuber, M; Gautschi, N; Oechslin, E; Widmer, V; Kiowski, W; Jenni, R
Abstract : OBJECTIVE: To evaluate the outcome of pregnancy in women with congenital shunt lesions. SETTING: Retrospective study in a tertiary care centre. METHODS: Pregnancy history was obtained by a standardised questionnaire and medical records were reviewed. PATIENTS: 175 women were identified, at a mean (SD) age of 42 (14) years. Pregnancies occurred in 126 women: 50 with an atrial septal defect, 22 with a ventricular septal defect, 22 with an atrioventricular septal defect, 19 with tetralogy of Fallot, and 13 with other complex shunt lesions. RESULTS: 309 pregnancies were reported by 126 woman (2.5 (1.6) pregnancies per woman). The shortening fraction of the systemic ventricle was 40 (8)%, and 98% were in New York Heart Association class I–II at last follow up. Spontaneous abortions occurred in 17% of pregnancies (abortion rate, 0.4 (0.9) per woman). Gestational age of the 241 newborn infants was 8.8 (0.8) months. There were no maternal deaths related to pregnancy. Pre-eclampsia and embolic events were observed in 1.3% and 0.6%, respectively of all pregnancies. Women with complex shunt lesions more often underwent caesarean section (70% v 15–30%, p = 0.005) and gave birth to smaller babies for equivalent gestation (2577 (671) g v 3016 (572) to 3207 (610) g, p < 0.05). The recurrence risk of congenital heart disease was 2.5%. CONCLUSIONS: The outcome of pregnancy is favourable in women with congenital shunt lesions if their functional class and their systolic ventricular function are good. Such patients can be reassured.